Translational implications: History and multilingualism in Henry V - M. Gomes da Torre (Ilha do Desterro)
William Shakespeare used as subjects for some of his plays episodes of the political history of England which occurred, mainly, in the periods traditionally designed as the Hundred Years’ War (1337- 1453) and the Wars of the Two Roses (1455-85). The former was characterized by great oscillations between military success and failure and was caused by the desire of some English kings who wanted to occupy the French throne, but it was equally desired by the common English people themselves, who already had a developing sense of nationalism, but, in addition, considered the French wars good opportunities to reduce the hardships of their daily living through the products of plundering and ransom usually associated with such wars. The initially surprisingly successful English invasions of France and the resounding victories in the battles of Crécy (1346), Poitiers (1356) and Azincourt (1415) filled the collective English soul with pride and survived in the memory of the people throughout the centuries. When Shakespeare used such historical matters in his plays, he did not but give voice to that national pride and offer his countrymen the flavour of glorious past times. The Wars of the Two Roses, on the contrary, also survived in the people’s memory, but as tragic episodes of a civil war in which two families—the House of York (symbolized by the white rose) and the House of Lancaster (symbolized by the red rose)—involved themselves in bloody fights for the English throne.